"Service‐learning makes it real": Assessing value and relevance in anthropology education. Issue 1 (May 2018) - SCHALGE, SUSAN; PAJUNEN, MATTHEW; BROTHERTON, JACLYN
Abstract: At Minnesota State University, Mankato, the Anthropology Department pursued service‐learning as a means of educating and engaging diverse publics. An assessment of the service‐learning program began after it became clear that standard course evaluations provided an inadequate assessment of service‐learning's efficacy. We employed a mixed‐ method, multiperspective approach, combining interview data gathered from students, faculty, community partners, and program coordinators to complement existing archival and survey data. Through these interviews and participant observation, we explore the pedagogy of service‐learning, its effectiveness, and the relationship among anthropological theory and practice. Our research identified three forms of value regarding student and community partner motivation. Additionally, we consider the role of culture in what constitutes value. One emergent theme, "realness, " was vital for enhancing student outcomes through providing embodied examples of concepts and practical experience in field methods. Service‐learning enhances comprehension through practical application, demonstrating the relevance of anthropology while improving students' learning outcomes.